In vivo Labeling of Constellations of Functionally Identified Neurons for Targeted in vitro Recordings - Lien, Anthony D.; Scanziani, Massimo (Frontiers in Neural Circuits, 2011)
Relating the functional properties of neurons in an intact organism with their cellular and synaptic characteristics is necessary for a mechanistic understanding of brain function. However, while the functional properties of cortical neurons (e.g., tuning to sensory stimuli) are necessarily determined in vivo, detailed cellular and synaptic analysis relies on in vitro techniques. Here we describe an approach that combines in vivo calcium imaging (for functional characterization) with photo-activation of fluorescent proteins (for neuron labeling), thereby allowing targeted in vitro recording of multiple neurons with known functional properties. We expressed photo-activatable GFP rendered non-diffusible through fusion with a histone protein (H2B–PAGFP) in the mouse visual cortex to rapidly photo-label constellations of neurons in vivo at cellular and sub-cellular resolution using two-photon excitation. This photo-labeling method was compatible with two-photon calcium imaging of neuronal responses to visual stimuli, allowing us to label constellations of neurons with specific functional properties. Photo-labeled neurons were easily identified in vitro in acute brain slices and could be targeted for whole-cell recording. We also demonstrate that in vitro and in vivo image stacks of the same photo-labeled neurons could be registered to one another, allowing the exact in vivo response properties of individual neurons recorded in vitro to be known. The ability to perform in vitro recordings from neurons with known functional properties opens up exciting new possibilities for dissecting the cellular, synaptic, and circuit mechanisms that underlie neuronal function in vivo.